Power plays : interior desires, exterior spaces - Artists collected - Desiron, Helena; Huybrechts, Liesbeth; Stevenheydens, Ive; Toubac, Tim (Hasselt : Platform Beeldende Kunsten Limburg Hasselt, 2007)
After Cage ; Bain, Mark ; Bibliotheek van Babel ; Bulourde, Gaëtan ; Casaer, Paul ; Claes, Marc ; Clicteur, Ann ; Coussement, Yves ; Dementieva, Alexandra ; Devens, Paul ; Devillé, Jozef ; Dondeyne, Luc ; Eerdekens, Fred ; Euba, Jon Mikel ; Excess ; Feyaerts, Wouter ; Geenen, Pieter ; Goiris, Geert ; Gubbels, Klaas ; Hendrickx, Niko ; Hynninen, Mikko ; Jacobs, Aernoudt ; Liekki, Rakel ; Light Play ; Meste, Philippe ; Serneels, Stefan ; Sites of Elasticity ; Smith, Gregg ; Tillieu, Iphigenia ; Vanagt, Sarah ; Vandebeek, Roel ; Visschers, Ellen ; Voet, Leen ; Whettnall, Sophie ; Wild Vlees ; Wuestenbergs, Gaston
boek